Modelo multicirtério de avaliação de treinamentos corporativos em modo e-learning - Berkenbrock, Jordana Paula Bonatto (2021)
The increasing advance and modernization of society, together with the expansion of the use of communication and information technologies, are directly affecting organizations, which requires increasingly updated, competent and skilled professionals. In this scenario, corporate learning gains new perspectives in the job market and the offer of training in the e-learning model has been increasingly common, regardless the kind or size of the organization. Considering the need for companies to have an evaluation system for training in the e-learning model, it is believed that this research will contribute to this knowledge gap having as its general objective to propose and apply a multi-criteria evaluation model to evaluate corporate training offered at a distance. The research was developed in five stages: bibliographic research, structuring of the model, presentation of the model, data collection and application of the model and presentation of the results. The model presented has four dimensions and fifteen criteria, which can be applied in whole or in part, depending on the organization's intentionality. The application of the model occurred in an organization in the banking area where twelve training sessions were evaluated in the four dimensions and seven criteria. Data processing was performed using the multi-criteria method FitTradeoff to determine the weights of each criterion and the TOPSIS method to rank the alternatives. As a result, a multi-criteria evaluation model was presented, which shows promise by helping companies and managers in the evaluation of corporate training in the e-learning model, in a practical and efficient way. It is intended that this model can be applied in different types of training and in different segments of companies, and can be a standardized form of assessment, or even be adapted according to the reality of each company.